2018
DOI: 10.5152/etd.2018.18128
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Pneumonia in Adults: What’s New Focusing on Epidemiology, Microorganisms and Diagnosis?

Abstract: Community-acquired pneumonia (CAP) is one of the most common causes of hospital admissions and death worldwide. The incidence and mortality of CAP are associated with the presence of comorbidities and increasing age. Streptococcus pneumoniae is the most frequent causative microorganism of CAP, although in many patients with CAP, the causative microorganism remains unknown. Currently, antimicrobial resistance is increasing, so the accurate diagnosis and determination of the causative microorganism are even more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
(38 reference statements)
0
9
0
3
Order By: Relevance
“…Community-acquired pneumonia (CAP) is one of the most common causes of hospital admissions and death worldwide. The incidence and mortality of CAP are associated with the presence of comorbidities and increasing age [65].…”
Section: Pneumoniamentioning
confidence: 99%
See 2 more Smart Citations
“…Community-acquired pneumonia (CAP) is one of the most common causes of hospital admissions and death worldwide. The incidence and mortality of CAP are associated with the presence of comorbidities and increasing age [65].…”
Section: Pneumoniamentioning
confidence: 99%
“…Using hospital data, pneumonia is one of the most frequent causes of hospitalization in adults. In developed countries, the main burden of hospitalized patients with CAP is in older patients with comorbidity, whereas in many developing countries, the main burden of hospitalized patients with CAP is among adults in the working age [65]. The World Health Organization reported that the average number of deaths related to CAP was approximately 700,000 deaths per year in developing countries [65].…”
Section: Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…A PAC é a principal causa de mortalidade listada entre as condições infecciosas no mundo e acarreta cerca de 1 milhão de internações hospitalares, causando enorme impacto nos recursos de saúde e representando um desafio em termos do diagnóstico e do tratamento. Sua incidência e mortalidade estão associadas ao aumento da idade e do surgimento de comorbidades (4). No Brasil, a PAC é a principal causa de internação no Sistema Único de Saúde.…”
unclassified
“…O conhecimento da etiologia das infecções mais comuns da PAC é importante para prescrição empírica inicial de antimicrobianos. Seguindo essa ideia, normalmente é prescrito um antimicrobiano de espectro mais amplo, o que pode elevar a possibilidade de toxicidade e de aumento da resistência bacteriana (4). Neste contexto, é sabido que Streptococcus pneumoniae é responsável por boa parte dos casos de pneumonia em adultos no mundo.…”
unclassified